Ancient Mesopotamia: green lessons from the past - Sen, Benita (New Delhi The Energy and Resource Institute, 2011)
Did you know that the Mesopotamians were the ones who came up with the idea of using wind energy to travel from one place to another? Or, that they were the first to build a network of canals to irrigate their fields? Journey across ancient Mesopotamia, as King Hammurabi guides little Teri through the paths of history, to learn many such interesting facts.
Keywords: Civilization; Manners and customs